Possible protective effect of alcoholic extract of Moringa oleifera on the skin in valproic acidadministered rats - YARAT, AYŞEN (My University, 2022)
Among the main functions of the skin are to protect the body from external factors, to provide water balance, to synthesize vitamin D and to remove various waste materials from the body. Drugs for the treatment of various diseases can adversely affect the structure and functions of the skin. Valproic acid/valproate (VPA) or 2-n-propylpentanoic acid is one of these drugs. Besides being used in the treatment of epilepsy and seizures, VPA is also effective in migraine, bipolar disorder, anxiety and other psychiatric disorders. Among the dermatological side effects of VPA, there are different effects such as hirsutism, hair loss, change in hair color, change in hair growth, and rarely skin rashes. Extracts from Moringa oleifera (M. oleifera) exhibit multiple nutraceutical or pharmacological functions, including anti-inflammatory, anti-oxidant, anticancer, hepatoprotective and neuroprotective functions. The oil obtained from the seed of this plant has cosmetic value and is known to be used as a moisturizer and skin care product in body and hair care. In this study, the possible protective effect of M.oleifera alcoholic extract on the skin in VPA-treated rats was investigated. Skin lipid peroxidation values increased significantly in the VPA group compared to the control group. Lipid peroxidation values were significantly reduced with the application of M. oleifera extract. M. oleifera extract may contribute to the prevention of dermatological side effects of antiepileptic drugs and the development of new therapeutics for skin health. This study was supported by Marmara University Scientific Research Projects Commission (Project No: TYL-2022-10423).
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)